2016
DOI: 10.1111/1475-6773.12504
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated with Home Health Care Referrals at Hospital Discharge: Results from the 2012 National Inpatient Sample

Abstract: As health policy changes influence postacute HHC, defining specific diagnoses and regional patterns associated with HHC is a first step to optimize postacute HHC services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…Our study of all Medicare fee‐for‐service beneficiaries hospitalized for HF discharged to SNF and subsequently discharged home found that patients who received HHC on discharge were less likely to be readmitted within 30 days than those discharged home without HHC. This is unexpected, as patients discharged with HHC are likely to have more functional impairments and had shorter SNF stays. The latter is a particularly salient finding as patients with shorter SNF stays theoretically may be at higher risk for readmission because they are fewer days out from hospital discharge and consequently may be less recovered from their acute illness than those with longer SNF stays.…”
Section: Discussionmentioning
confidence: 96%
“…Our study of all Medicare fee‐for‐service beneficiaries hospitalized for HF discharged to SNF and subsequently discharged home found that patients who received HHC on discharge were less likely to be readmitted within 30 days than those discharged home without HHC. This is unexpected, as patients discharged with HHC are likely to have more functional impairments and had shorter SNF stays. The latter is a particularly salient finding as patients with shorter SNF stays theoretically may be at higher risk for readmission because they are fewer days out from hospital discharge and consequently may be less recovered from their acute illness than those with longer SNF stays.…”
Section: Discussionmentioning
confidence: 96%
“…42 Another study that examined 1.1 million discharges of Medicare patients aged ≥65 years found that patients who were referred to home health care at discharge were more likely to be older, female, live in an urban location, have lower income, have a longer length of stay, have higher illness severity scores, have a diagnosis of heart failure or sepsis, and be hospitalized in New England (vs the Pacific). 15 Hartman et al 2007 analyzed the 2002 Medicare home health care data and found that although the proportion of Medicare beneficiaries nationwide who lived in areas with few home health care agencies was relatively low, less than 1% of urban beneficiaries lived in ZIP codes with no or low use of home health care compared to more than 17% of the most rural beneficiaries. 43 Unlike these previous studies that focused on the patient level, we focused on the county, an important and actionable perspective since improvement efforts require system changes beyond the reach of individual healthcare practitioners and patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 A majority of older patients referred for HHC at hospital discharge have Medicare insurance, which requires that patients meet the following three conditions for skilled HHC services to be reimbursable: 1) are under the care of a physician, 2) have a need for a skilled HHC service (e.g., nursing, physical therapy) certified by a physician, and 3) are homebound (e.g., have great difficulty leaving home due to a medical condition). 5,6 Patients referred for HHC may be particularly vulnerable after hospital discharge, as they are nearly 3 years older, have one additional comorbidity, and have higher severity of illness than patients discharged home without HHC. 5 Readmission rates for HHC patients are higher than the national average for high-risk conditions such as heart failure (HF), in which 30-day readmission rates for Medicare beneficiaries discharged with HHC are as high as 23-26%, 7,8 compared to a 21.9% overall national average for Medicare patients discharged with HF.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Patients referred for HHC may be particularly vulnerable after hospital discharge, as they are nearly 3 years older, have one additional comorbidity, and have higher severity of illness than patients discharged home without HHC. 5 Readmission rates for HHC patients are higher than the national average for high-risk conditions such as heart failure (HF), in which 30-day readmission rates for Medicare beneficiaries discharged with HHC are as high as 23-26%, 7,8 compared to a 21.9% overall national average for Medicare patients discharged with HF. 9…”
Section: Introductionmentioning
confidence: 99%